HUBUNGAN ANTARA LAMA MENJALANI HEMODIALISIS DAN RISIKO MENDERITA SLEEP APNEA - Handy Darmawan,* Astuti,** Ahmad Asmedi,** Abdul Gofir,** Bambang Djarwoto*** (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION THE INCIDENCE OF CHRONIC KIDNEY DISEASE CKD IS RISING IN INDONESIA HEMODIALYSIS HD IS THE MOST FREQUENT KIDNEY REPLACEMENT THERAPY USED FOR CKD PATIENTS IN INDONESIA SLEEP APNEA SA IS COMMONLY FOUND IN HD PATIENT IT DECREASES THE QUALITY OF LIFE AMONG THEM AND IS STILL UNDERDIAGNOSED